2014
DOI: 10.1021/ja510475n
|View full text |Cite
|
Sign up to set email alerts
|

A New Organocatalytic Concept for Asymmetric α-Alkylation of Aldehydes

Abstract: The organocatalytic asymmetric α-alkylation of aldehydes by 1,6-conjugated addition of enamines to p-quinone methides is described. Employing a newly developed class of chiral secondary amine catalysts, α-diarylmethine-substituted aldehydes with two contiguous stereocenters have been synthesized in a simple manner with good diastereocontrol and excellent enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(76 citation statements)
references
References 56 publications
(20 reference statements)
0
74
0
Order By: Relevance
“…We envisioned that p ‐QMs could be a second Michael acceptor in an RC reaction (Scheme b). In the aforementioned pieces of work,,, p ‐QMs could be activated by chiral Brønsted acid through an intermolecular H‐bonding interaction, resulting in remote stereocontrol. Notably, phosphines are also elegant catalysts for the RC reaction .…”
Section: Methodsmentioning
confidence: 99%
“…We envisioned that p ‐QMs could be a second Michael acceptor in an RC reaction (Scheme b). In the aforementioned pieces of work,,, p ‐QMs could be activated by chiral Brønsted acid through an intermolecular H‐bonding interaction, resulting in remote stereocontrol. Notably, phosphines are also elegant catalysts for the RC reaction .…”
Section: Methodsmentioning
confidence: 99%
“…For the organocatalytic enantioselective a-arylation of aldehydes Caruana et al reported asymmetric organocatalytic 1, 6-conjugate addition of para-quinone methides to aldehydes (Scheme 58). [91] Using the newly developed chiral secondary amine organocatalyst (40 e) a-diarylmethine-substituted aldehydes with two contiguous stereocenters can be prepared in high yield (up to 90 %y ield) and stereoselectivity (up to 11:1 d.r.a nd 99 % ee). The authors noted that if the chiral secondary amine organocatalyst (40 e) was used, although high enantioselectivity could be obtained, the corresponding diastereoselectivity was low probably owing to poor control over the approach of the well shielded enamineo ft he corresponding aldehyde to the para-quinone methides (Scheme 59).…”
Section: Miscellaneous Other Moleculesmentioning
confidence: 99%
“…Michael addition, 11 and (x) radical-triggered alkylation. 12 However, some of these transformations suffer from the use of stoichiometric metallic bases, less environmental-benign alkyl halides or pre-functionalized reagents.…”
Section: Introductionmentioning
confidence: 99%